Lead corrosion inhibition by cedrus atlantica as a green inhibitor in 0.1M Na2CO3 solution - Elmiziani, Inaam; Houbairi, Sara; Essahli, Mohamed; Lhaloui, Saadia; Lamiri, Abdeslam (International Journal of Advanced Chemistry, 2017)
The inhibition of lead corrosion in 0.1 M Na2CO3 solution with the essential oil of Atlas cedar was studied by polarization and impedance. The studies of polarization showed that the essential oil of Cedrus atlantica acts as a cathodic inhibitor. The different thermodynamic and kinetic parameters were calculated to understand the energy changes associated during the inhibition process. The effectiveness increases with the concentration to reach 70% at concentration of 2000 ppm.